Into the fury - Martin, Kat (Martin, Kat. BOSS, Inc. novel., 2016)
After a group of lingerie models are threatened, Ethan Brodie is brought on to protect them, and when one is murdered, he finds himself drawn closer to the breathtaking Valentine Hart, as he gets closer to the answers he needs to solve the crime.